Dangerous lives, frail bodies, alien practices: Reflections on a migrant hunger-strike - Ζαββού Αλεξάνδρα (The Greek Review of Social Research, 2013)
In January 2011 a group of 300 male migrants began a 45-day hunger strike in Athens and Thessaloniki demanding from the Greek government their rights to legal work and residence in Greece. Taking this event – and the surrounding public debate – as starting point, I will consider the possibility of understanding the migrant hunger-strike as a biopolitical practice of citizenship that confronts the limits of what can, and can’t, be culturally legible and ethically sanctioned as political self-determination.